Relatively Wild Urban Parks Can Promote Human Resilience and Flourishing: A Case Study of Discovery Park, Seattle, Washington - Lev, Elizabeth; Kahn, Peter H.; Chen, Hanzi; Esperum, Garrett (Frontiers in Sustainable Cities, 2020)
Human interaction with nature is vital for physical health and mental well-being, and positions a community to be resilient to urban stressors. Yet urban development continues to put pressures on natural areas within urban boundaries. As a case in point, Seattle's largest park, Discovery Park, of over 500 acres, is often under threat of some form of development. The central question of this study was whether the benefits to visitors of Discovery Park depend, in no small measure, on the park's very size and relative wild landscape. Toward addressing this question, 320 participants provided written narratives (through our web portal) about the meaningful ways in which they interacted with nature at Discovery Park. Each individual narrative was then analyzed and coded using an Interaction Pattern (IP) approach, which provides characterizations of human-nature interaction that have ontogenetic and phylogenetic significance. Results revealed 520 Interaction Patterns (IPs). The most frequently occurring IPs clustered under the keystone IPs of Encountering Wildlife (27%), Following Trails (14%), Walking to Destination Spots in Nature (8%), Gazing out at the Puget Sound or Mountains (6%), Walking Along Edges of Beach or Bluffs (5%), and Walking with Dogs (4%). Results also revealed that visitors' meaningful interactions with nature in Discovery Park depended on the park's relative wildness. For example, (a) 77% of participants' IPs depended on Discovery Park's relative wildness; (b) of the participants who specified an especially meaningful experience with nature, 95% of them had an interaction that depended on Discovery Park's relative wildness; and (c) of the participants whose IPs were linked to other aspects of the nature in the park or to their own positive mental states, 95 and 96%, respectively, had an interaction that depended on Discovery Park's relative wildness. Discussion focuses on how human interaction with large and relatively wild urban parks helps reverse the trend of environmental generational amnesia, and a domination worldview, and thus should be prioritized in urban planning.